(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Athletes must demonstrate robust cognitive skills in order to attain the ambitious objective of sportsmanship, which has the potential to have a transformative impact on individuals’ lives outside the realm of athletics. According to the author, athletes make decisions by evaluating their current sporting situation and selecting the best suitable course of action based on that context. Although a skilled manager can successfully complete a given the process is intricate and depends on the athlete’s proficiency in environmental planning, strategic action, and selective responsiveness to specific circumstances. Many individuals believe that engaging in sports at early stages of life contributes to the development of positive habits and essential life skills. The objective of this paper was to conduct a survey among student athletes in order to get their perspectives on how athletics might contribute to the development of crucial soft skills such as leadership and management. Historically, managers depended on skills such as efficient allocation of time, strategic planning, mental toughness, and flexibility. The research emphasises the significance of play in fostering crucial life skills in children, including proficient decision making, efficient time management, strategic planning, resilience, and adaptability. Additionally, it emphasises the beneficial influence of sports on students’ acquisition of these skills.